Desenvolvimento de um sistema de aquisição de informações volumétricas usando métodos de triangulação a laser e campo de visão variável - França, João Guilherme Darezzo Martins de (2004)
The most efficient 3D acquisition systems use the principle of laser triangulation or the principle of time of flight TOF. In the systems based on triangulation, the range and the depth variation are very limited, but it has a great precision. On the other hand the opposite occurs to the TOF systems where it has a low precision, and a great range and depth variation. This work describes a project of a 3D acquisition system, with greater precision and range than traditional laser triangulation 3D scanners, and it s as versatile as TOF systems. An initial prototype of this system had been implemented.